Local pair model for the analysis of tunneling and photoemission experiments in the normal state of high TC superconductors - Alascio, Blas Rafael; Allub, Ricardo; Proetto, Cesar Ramón; Ventura, C. I. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Alascio, Blas Rafael Comisión Nacional de Energía Atómica; Argentina